“White Jihad” and “White Sharia”: Jihadism as an Instrument of Intra-Extremist Outbidding among Right-Wing Extremists - Laryš, Martin (Terrorism and political violence, 2024)
Militant right-wing extremists frequently victimize Islam and Muslims, who are denigrated as violent criminals and terrorists. Muslim immigrants are primary targets of hate crimes committed by right-wing extremists. Surprisingly and counter-intuitively, some right-wing extremists admire jihadists and seek inspiration from jihadism. The extant literature explains it by focusing on the ideological overlapping, fusion, and fluidity between various extremist beliefs. However, such concepts fail to explain why some right-wing extremists endorse jihadi propaganda and violence while others do not. The article introduces the concept of intra-extremist outbidding—borrowing concepts and imageries from diametrically opposed types of extremism and belief systems to outbid competing groups from their own milieu—as a valuable explanation of why some most extreme right-wing groups compete for devoted membership by endorsing jihadi violence and jihadism.